2021
DOI: 10.3390/diagnostics11101858
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Progression Time in Pancreatic Cancer including Carcinoma In Situ Based on Magnetic Resonance Cholangiopancreatography Findings

Abstract: Background: Pancreatic cancer (PC) exhibits extremely rapid growth; however, it remains largely unknown whether the early stages of PC also exhibit rapid growth speed equivalent to advanced PC. This study aimed to investigate the natural history of early PCs through retrospectively assessing pre-diagnostic images. Methods: We examined the data of nine patients, including three patients with carcinoma in situ (CIS), who had undergone magnetic resonance cholangiopancreatography (MRCP) to detect solitary main pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Magnetic resonance (MR) imaging of the pancreas along with MR cholangiopancreatography (MRCP) allow for accurate detection of early PDAC by facilitating morphological analysis of pancreatic ductal changes (64). A recent study found that incipient MPD stenosis on pre--diagnostic MRCP can be detected 26-49 months prior to pancreatic tumor detection on any of the imaging methods (CT, MR, or EUS) (77).…”
Section: Ct -Computed Tomography; Mri -Magnetic Resonance Imaging; Mr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance (MR) imaging of the pancreas along with MR cholangiopancreatography (MRCP) allow for accurate detection of early PDAC by facilitating morphological analysis of pancreatic ductal changes (64). A recent study found that incipient MPD stenosis on pre--diagnostic MRCP can be detected 26-49 months prior to pancreatic tumor detection on any of the imaging methods (CT, MR, or EUS) (77).…”
Section: Ct -Computed Tomography; Mri -Magnetic Resonance Imaging; Mr...mentioning
confidence: 99%
“…This is valuable for clinicians as it indicates that EUS can also exclude pancreatic cancer. In patients with PDAC it is frequently used as a complementary staging tool to evaluate regional lymph nodes, define the degree of tumor--vascular involvement, or secure a definitive cytologic or histologic diagnosis (77,83).…”
Section: Endoscopymentioning
confidence: 99%
“…Despite substantial efforts in cancer research, the five-year survival rate for pancreatic cancer remains extremely low, at approximately 10%, underscoring the urgent need for novel therapeutic strategies [3]. Pancreatic cancer is characterized by its rapid progression [4], late-stage diagnosis [4], and resistance to conventional therapies [5]. The majority of patients present with advanced disease, precluding curative surgical intervention and rendering systemic therapies less effective [6].…”
Section: Introductionmentioning
confidence: 99%